2017
DOI: 10.1016/j.actamat.2016.10.037
|View full text |Cite
|
Sign up to set email alerts
|

A lightweight single-phase AlTiVCr compositionally complex alloy

Abstract: A lightweight (5.06 g.cm-3) AlTiVCr compositionally complex alloy consisting of four elements is presented. Interest in the system is due to its microstructural uniformity and the use of commodity elements. The focus of the present work was to highlight the systematic microstructural and chemical characterizationand the information gained by application of various physical and modeling techniques in concertin the context of complete characterization of compositionally complex alloys. Herein, analysis of as-cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(64 citation statements)
references
References 57 publications
1
61
0
2
Order By: Relevance
“…In addition, it is noted that both the flower-like dendrites and Figure 3 gives the elemental distributions of the Al 1.12 alloy (S5) measured by EMPA, from which it could be found that much greater amounts of Al and Ni are aggregated in the flower-like dendrites, and the other inter-dendrites contain much greater contents of Fe and Cr. The measured compositions of the flower-like dendrites and the inter-dendrites are Al 26 The specific microscopic morphologies of BCC/B2 phases in this HEA series are revealed by highly-magnified SEM images (Figure 4), in which the disordered BCC and its ordered B2 phases always exist coherently. Even in the FCC-based HEAs of Al 0.41 (S1, Figure 4a) and Al 0.57 (S2, Figure 4b), the BCC and B2 phases are coherent in the inter-dendrites with a weave-like morphology caused by spinodal decomposition.…”
Section: Microstructural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is noted that both the flower-like dendrites and Figure 3 gives the elemental distributions of the Al 1.12 alloy (S5) measured by EMPA, from which it could be found that much greater amounts of Al and Ni are aggregated in the flower-like dendrites, and the other inter-dendrites contain much greater contents of Fe and Cr. The measured compositions of the flower-like dendrites and the inter-dendrites are Al 26 The specific microscopic morphologies of BCC/B2 phases in this HEA series are revealed by highly-magnified SEM images (Figure 4), in which the disordered BCC and its ordered B2 phases always exist coherently. Even in the FCC-based HEAs of Al 0.41 (S1, Figure 4a) and Al 0.57 (S2, Figure 4b), the BCC and B2 phases are coherent in the inter-dendrites with a weave-like morphology caused by spinodal decomposition.…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…This new type of alloys has attracted much attention due to the formation of simple crystalline structures, such as face-centered cubic (FCC)-, body-centered cubic (BCC)-, and close-packed hexagonal (HCP)-solid solutions, as well as their derivatives, instead of complex intermetallic compounds [6][7][8]. Until now, many HEAs have been reported in diverse systems, e.g., CoCrFeNi-based HEAs [9][10][11][12][13][14], Al-TMs HEAs (TMs: transition metals) [15][16][17][18][19][20][21][22][23], and refractory HEAs [24][25][26][27]. The special structures render HEAs with the unique performance of excellent mechanical properties and superior corrosion-/oxidation-resistances, as examplified by the fact that the single FCC CoCrFeMnNi HEA shows a remarkably high fracture toughness that outperforms all conventional alloys at cryogenic temperatures [3,6,11].…”
Section: Introductionmentioning
confidence: 99%
“…They investigated the corrosion of the Cu 0.5 NiAlCoCrFeSi alloy in H 2 SO 4 and NaCl solutions and compared it with the corrosion characteristics of an austenitic stainless steel (AISI 304 SS). The concentrations of the solutions were varied from 0.1 to 1 M, and it was observed that the Cu 0.5 NiAlCoCrFeSi alloy had a lower corrosion rate (as defined by the corrosion current density, i corr ) than 304SS in all the test solutions.…”
Section: Aqueous Corrosion Of Heasmentioning
confidence: 99%
“…Continued research has however highlighted that numerous socalled HEAs, such as the Mo 0.5 AlNbTa 0.5 TiZr system, did not have high configurational entropies and present the formation of secondary phases (rather than just solid solution phases). Therefore, a more general description of such alloy systems has emerged, with the more general naming and definition being compositionally complex alloys (CCAs), 4,5 which is the preferred naming used throughout this review.…”
Section: Introductionmentioning
confidence: 99%
“…The low temperature phase separation was confirmed by the experiment. [30] It is desired to have more advanced experimental technique to verify the spinodal Very recently Qiu et al [31] studied the lightweight single-phase Al 1 Cr 1 Ti 1 V 1 alloy. A simple single-phase microstructure was revealed in the as-cast alloy via conventional and scanning transmission electron microscopy.…”
Section: Typical Bcc Systemsmentioning
confidence: 99%